Postmodernism in Contemporary Educational Practices - Lukoševičiūtė, Aušra (Jaunųjų mokslininkų darbai, 2017)
Postmodernism is marked by information, an increasing competition and radical changes in the education sector. Moral and spiritual progress fails to keep pace with scientific and technological progress. That is evident in educational practices, thus, new challenges arise because of a lack of attention to personality. Modernity, characterised by objectivity and rationality, has been challenged by post modernity which seeks to reconstruct existing forms of thinking and promotes a new worldview. The author discusses modern educational practices in the context of postmodernism. She analyses some aspects of postmodernism, its marks in contemporary education. Drawing on the proponents and opponents of postmodernism, the author states that postmodernism influences changes in the content, methods of teaching as well as in teachers’ approaches to teaching. Nowadays much attention in education is given to self-expression, interpretation, a pluralistic worldview, consumerist values. The conclusion has been drawn that changes in education should be seen as a natural process that affects personality development, cognitive development, self-realization.